Paternal effects correlate with female reproductive stimulation in the polyandrous ladybird Cheilomenes sexmaculata - Mirhosseini, M. A.; Michaud, J. P.; Jalali, M. A.; Ziaaddini, M. (My University, 2014)
Components of male seminal fluids are known to stimulate fecundity and fertility in females of numerous insect species and paternal effects on offspring phenotype are also known, but no studies have yet demonstrated links between male effects on female reproduction and those on progeny phenotype. In separate laboratory experiments employing 10-day-old virgin females of Cheilomenes sexmaculata (F.), we varied male age and mating history to manipulate levels of male allomones and found that the magnitude of paternal effects on progeny phenotype was correlated with stimulation of female reproduction. Older virgin males remained in copula longer than younger ones, induced higher levels of female fecundity, and sired progeny that developed faster to yield heavier adults. When male age was held constant (13 days), egg fertility declined as a function of previous male copulations, progeny developmental times increased, and the adult weight of daughters declined. These results suggest that male epigenetic effects on progeny phenotype act in concert with female reproductive stimulation; both categories of effects increased as a consequence of male celibacy (factor accumulation), and diminished as a function of previous matings (factor depletion). Male factors that influence female reproduction are implicated in sexual conflict and parental effects may extend this conflict to offspring phenotype. Whereas mothers control the timing of oviposition events and can use maternal effects to tailor progeny phenotypes to prevailing or anticipated conditions, fathers cannot. Since females remate and dilute paternity in polyandrous systems, paternal fitness will be increased by linking paternal effects to female fecundity stimulation, so that more benefits accrue to the male's own progeny.
Citation: Mirhosseini, M., Michaud, J., Jalali, M., & Ziaaddini, M. (2014). Paternal effects correlate with female reproductive stimulation in the polyandrous ladybird Cheilomenes sexmaculata. Bulletin of Entomological Research, 104(4), 480-485. https://doi.org/10.1017/S0007485314000194
Keywords: Development; Fecundity; Fertility; Sexual conflict; Cheilomenes sexmaculata